2016
DOI: 10.1016/j.mod.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

What shapes the oral jaws? Accommodation of complex dentition correlates with premaxillary but not mandibular shape

Abstract: These differences in the jaw skeleton have likely evolved due to different feeding strategies utilised by each species. Our results show that premaxillae shape correlates strongly with the development of complex dentitions unlike in the mandible. This study provides important insights into the relationship between jaw and tooth development in bony fishes and suggests that these mechanisms may be similar amongst vertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The cartilaginous elements of the developing jaw structures of this species can be observed as early as 2.5 dpf in both morphs (Hinaux et al, ). The A. mexicanus lower jaw develops from Meckel's cartilage; the premaxillary and the maxillary bones ossify in association with the ethmoid and palatoquadrate cartilage (Atukorala and Franz‐Odendaal, ; Hammer et al, ). These cartilaginous elements are gradually replaced by intramembranous and perichondral ossification (Atukorala and Franz‐Odendaal, ).…”
Section: Bones With Life‐long Tooth Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…The cartilaginous elements of the developing jaw structures of this species can be observed as early as 2.5 dpf in both morphs (Hinaux et al, ). The A. mexicanus lower jaw develops from Meckel's cartilage; the premaxillary and the maxillary bones ossify in association with the ethmoid and palatoquadrate cartilage (Atukorala and Franz‐Odendaal, ; Hammer et al, ). These cartilaginous elements are gradually replaced by intramembranous and perichondral ossification (Atukorala and Franz‐Odendaal, ).…”
Section: Bones With Life‐long Tooth Replacementmentioning
confidence: 99%
“…These cartilaginous elements are gradually replaced by intramembranous and perichondral ossification (Atukorala and Franz‐Odendaal, ). Hammer et al () analyzed the bone stain growth series of the jaw bones of the surface morphs and found that the premaxilla ossified first followed by the dentary and the maxilla (Hammer et al, ). The primary ossification areas in SF were in a different sequence from those observed in zebrafish jaw development.…”
Section: Bones With Life‐long Tooth Replacementmentioning
confidence: 99%
“…As noted earlier, unique suites of genes pattern upper and lower jaws; the genetic integration of tooth/jaw tissues may also be jaw specific (Boughner and Uppal, ). Different programs may integrate Evo‐Devo change between each jaw and its dentition, including responses to feeding strategies (Boughner, ; Hammer et al., ). Thus, developmental genetic variation is raw material for selection while, as will be explained just below, oral function helps integrate growing jaws, catalyzes phenotypic plasticity in an individual, and drives adaptive oral macroevolution in a population.…”
Section: Malocclusion: a Point Of Human Evo‐devo Pride?mentioning
confidence: 99%
“…Many of the same genes are conserved in both dentitions (Yamanaka, Iwai, Uemura, & Goto, ) yet some of these genes are differently expressed in developing maxillary versus mandibular teeth (Ferguson, Tucker, & Sharpe, ; Jia et al, ; Thomas et al, ). Recent work in fish found that premaxilla shape correlated strongly with dental phenotype while mandible shape did not, evidence of jaw‐specific patterns of tooth/jaw integration (Hammer, Atukorala, & Franz‐Odendaal, ). Such differences may help explain how upper and lower teeth can evolve independently in terms of size, shape, and number.…”
Section: Introductionmentioning
confidence: 99%